Complexity and asynchrony of climatic drivers and environmental responses during the Last Glacial-Interglacial Transition (LGIT) in north-west Europe. (15th December 2020) - Abrook, Ashley M.; Matthews, Ian P.; Candy, Ian; Palmer, Adrian P.; Francis, Chris P.; Turner, Lucy; Brooks, Stephen J.; Self, Angela E.; Milner, Alice M.
Abstract: The Last Glacial-Interglacial Transition ( ca 16–8 ka BP) in north-west Europe is an important period of climatic change where millennial-scale climatic evolution led to environmental reorganisation. Imprinted upon these long-term changes are a series of short-lived, centennial-scale events that appear to be spatially and temporally complex across Europe. The complexity of environmental change in response to these climatic events is poorly understood because of a paucity of paired investigations that provide evidence of both driver and response variables. We present a high-resolution palynological, charcoal and stable isotopic record alongside chironomid-inferred temperature data from Tirinie, south-east Grampian Highlands, Scotland. The record is stratigraphically and chronologically constrained using tephra and radiocarbon dating. The isotopic and chironomid data reveal centennial-scale climatic deteriorations at ca 14.0; 13.2 and 11.4 cal ka BP. In response to these cooling events, vegetation became more open, fire frequency increased and landscape erosion was common. The reconstruction of both climate and environment reveals asynchrony in the phasing of annual and summer temperature variability, vegetation change and fire for each climatic event. Whilst responses appear strongest following the convergence of annual and summer temperature variability across all events, the ca 13.2 ka BP event reveals a two-stage environmental and fire response to climatic change, and the ca 11.4 ka BP event exhibits environmental change in the absence of summer temperature variability. The data further suggests that fire is an integral component of abrupt climatic change in this part of north-west Europe. Highlights: Multi-proxy study using palynology, charcoal, stable isotopes, chironomids. Annual and summer temperature variability drive environmental responses over abrupt climatic events. Hydrology is an unknown component driving vegetation change. Climatic variability and environmental responses are asynchronous across climatic events during the LGIT. Fire is an agent of landscape change within abrupt climatic events during the LGIT.